Systematic Review of Plasmid AmpC Type Resistances in Escherichia coli and Klebsiella pneumoniae and Preliminary Proposal of a Simplified Screening Method for ampC - Enrique Rodríguez-Guerrero; Juan Carlos Callejas-Rodelas; José María Navarro-Marí; José Gutiérrez-Fernández (Microorganisms, 2022)
Beta-lactamase (BL) production is a major public health problem. Although not the most frequent AmpC type, AmpC-BL is increasingly isolated, especially plasmid AmpC-BL (pAmpC-BL). The objective of this study was to review information published to date on pAmpC-BL in Escherichia coli and Klebsiella pneumoniae, and on the epidemiology and detection methods used by clinical microbiology laboratories, by performing a systematic review using the MEDLINE PubMed database. The predictive capacity of a screening method to detect AmpC-BL using disks with cloxacillin (CLX) was also evaluated by studying 102 Enterobacteriaceae clinical isolates grown in CHROMID ESBL medium with the addition of cefepime (FEP), cefoxitin (FOX), ertapenem (ETP), CLX, and oxacillin with CLX. The review, which included 149 publications, suggests that certain risk factors (prolonged hospitalization and previous use of cephalosporins) are associated with infections by pAmpC-BL-producing microorganisms. The worldwide prevalence has increased over the past 10 years, with a positivity rate ranging between 0.1 and 40%, although AmpC was only detected when sought in a targeted manner. CMY-2 type has been the most prevalent pAmpC-BL-producing microorganism. The most frequently used phenotypic method has been the double-disk synergy test (using CLX disks or phenyl-boronic acid and cefotaxime [CTX] and ceftazidime) and the disk method combined with these inhibitors. In regard to screening methods, a 1-µg oxacillin disk with CLX showed 88.9% sensitivity, 100% specificity, 100% positive predictive value (PPV), 98.9% negative predictive value (NPV), and 98.9% validity index (VI). This predictive capacity is reduced with the addition of extended-spectrum beta-lactamases, showing 62.5% sensitivity, 100% specificity, 100% PPV, 93.5% NPV, and 94.1% VI. In conclusion, there has been a worldwide increase in the number of isolates with pAmpC-BL, especially in Asia, with CMY-2 being the most frequently detected pAmpC-BL-producing type of microorganism. Reduction in its spread requires routine screening with a combination of phenotypic methods (with AmpC inhibitors) and genotypic methods (multiplex PCR). In conclusion, the proposed screening technique is an easy-to-apply and inexpensive test for the detection of AmpC-producing isolates in the routine screening of multidrug-resistant microorganisms.